1996
DOI: 10.33584/jnzg.1996.58.2199
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of perennial legume species in drought-prone, North and South Island sites

Abstract: The establishment from seed of 8 perennial legumes was investigated in 3 trials in drought-prone regions. Two trials, in central Hawke's Bay, aimed to determine the extent of establishment of 6 test species (Astragalus cicer, Coronilla varia, Dorycnium hirsutum, Dorycnium pentaphyllum, Lotus corniculatus, Lotus tenuis) and 2 standard species (Medicago sativa, Trifolium repens). The third trial, in Central Otago, aimed to identify the most effective strain of Rhizobium loti for nodulating D. hirsutum in the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A proposed role for Dorycnium species is as a standing ‘haystack’, to provide forage during periods of low feed supply (Wills, 1983; Douglas et al. , 1996b) which occur in late summer and autumn in southern Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proposed role for Dorycnium species is as a standing ‘haystack’, to provide forage during periods of low feed supply (Wills, 1983; Douglas et al. , 1996b) which occur in late summer and autumn in southern Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the tolerance of Dorycnium species to drought (Wills, 1983; Douglas et al. , 1996b), it has been suggested that their role in grazing systems could be the provision of standing green forage during times of shortage of forage.…”
Section: Introductionmentioning
confidence: 99%
“…The use of woody vegetation as forage has long been recognized [23][24][25][26][27][28]. Shrubs are used by farmers to lengthen the grazing season and can better tolerate poor soils and drought conditions where other vegetation finds growth difficult [29].…”
Section: Livestock Foragingmentioning
confidence: 99%
“…Some species of Astragalus L. (e.g. Cicer milkvetch) have shown potential in dry hill country (Douglas et al 1996). This legume genus comprises c. 3000 species and, while a number of these species are toxic for livestock (Rios & Waterman 1997), some others may be suitable for New Zealand hill country.…”
Section: Novel Species and New Germplasm For Desirable Traitsmentioning
confidence: 99%